2014
DOI: 10.1111/ene.12380
|View full text |Cite
|
Sign up to set email alerts
|

Headache‐attributed burden and its impact on productivity and quality of life in Russia: structured healthcare for headache is urgently needed

Abstract: Headache is common, burdensome and costly in Russia and, manifestly, poorly mitigated by existing healthcare. Structured healthcare services for headache need to be urgently put in place.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

7
65
2
11

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(88 citation statements)
references
References 37 publications
7
65
2
11
Order By: Relevance
“…Generally, it has been reported that female sufferers tend to outnumber male nearly 3 to 1 [4-6]. The disease brings about heavy socioeconomic burden [7-9] and leads to low quality of life [3, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…Generally, it has been reported that female sufferers tend to outnumber male nearly 3 to 1 [4-6]. The disease brings about heavy socioeconomic burden [7-9] and leads to low quality of life [3, 10]. …”
Section: Introductionmentioning
confidence: 99%
“…The number of diseases related to lifestyle factors as stress, obesity [1][2][3], excessive consumption of industrialized food containing additives, colorings, trans fats, and other ingredients [4][5][6][7], as well heavy workload [8], sedentary lifestyle, and environmental pollutants has been strongly increased [9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…Средняя стоимость лечения ГБ в нашей стране в 2014 г. составляла 455-494 руб. в месяц на 1 пациента [7,8].…”
unclassified